The Vital Role of Community Nursing in Managing Schizophrenia - Khalaf, Bakheet; Ali, Safaa; Taghred, Magda (STIKes Al-Ma'arif Baturaja, 2025)
Community nursing plays a pivotal role in managing schizophrenia by providing continuous care, education, and advocacy within society. Nurses ensure treatment adherence, monitor patients, and offer crisis intervention to prevent relapses. They also combat stigma through public awareness campaigns and promote social inclusion by connecting patients with vocational and rehabilitation programs. By collaborating with families, healthcare providers, and policymakers, community nurses enhance long-term recovery and improve patients' quality of life. Their holistic approach bridges gaps in mental healthcare, making services more accessible and effective. Ultimately, community nursing empowers individuals with schizophrenia to achieve stability and reintegrate into society.